Estimation of ground reaction forces from markerless kinematics and comparison against measured force plate data - Colyer, S.; Needham, L.; Evans, M.; Wade, L.; Cosker, D.; Cazzola, D.; McGuigan, P.; Bilzon, J. (ISBS Proceedings Archive (Michigan), 2023)
This study investigated how accurately ground reaction forces (GRFs) can be estimated from body centre of mass (BCOM) motion derived using markerless motion capture. Fifteen participants performed a countermovement jump (CMJ) on, and a running trial across, force plates. Kinematics captured using markerless and marker-based systems were used to drive IK-constrained OpenSim models. The resulting BCOM displacements were double differentiated to inversely estimate GRFs and compared to force plate data. Markerless-derived estimates were similar to measured GRFs (RMSD = ~70-150 N) and vertical peak force, impulse and rate of force development were also accurately estimated (effect sizes < 0.2), similarly to marker-based outputs. Our markerless workflow shows promise for the estimation of vertical GRF parameters out in the field, without markers or force plates.